Bioethanol Production from Waste Paper - Thakare, Komal; Trivedi, Minal (International Journal of Scientific Research in Biological Sciences, 2021)
The municipal waste constitutes paper as major part of the solid waste. Due to shrinking landfill capacity; it has become tough to manage this solid waste. The waste paper considered here is the newspaper along with the paper used in offices for printing & photocopying. The waste paper is rich in cellulose which could serve as substrate for bioethanol production. This would lead to reduction of greenhouse gases which are released in traditional way of ethanol production. In this study, an attempt was made to convert the cellulose, a sugar into ethanol via fermentation process. Before the actual fermentation, the paper was pre-treated and hydrolyzed with 5% conc.H2SO4 at 121°C for 30 minutes. The fermentation was carried out using S.cerevisiae. The alcohol was purified using distillation and the various parameters like specific gravity, odor, yield etc. were estimated.